The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2478/jvetres-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of goose parvovirus and duck circovirus coinfection in ducks

Abstract: IntroductionCoinfection of goose parvovirus (GPV) and duck circovirus (DuCV) occurs commonly in field cases of short beak and dwarfism syndrome (SBDS). However, whether there is synergism between the two viruses in replication and pathogenicity remains undetermined.Material and MethodsWe established a coinfection model of GPV and DuCV in Cherry Valley ducks. Tissue samples were examined histopathologically. The viral loads in tissues were detected by qPCR, and the distribution of the virus in tissues was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Interestingly, in the more recent study, nGPV with distinct mutation pattern in Vp3 protein was isolated from feather sacks of ducks suffering from feather shedding syndrome that is caused by DuCV [ 26 ]. Recently, the effect of co-infections was studied in detail in experimental settings [ 27 ]. It was observed that after the initial lower viral loads, the loads of both nGPV and DuCV in dually infected birds were higher compared to those infected with only one pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the more recent study, nGPV with distinct mutation pattern in Vp3 protein was isolated from feather sacks of ducks suffering from feather shedding syndrome that is caused by DuCV [ 26 ]. Recently, the effect of co-infections was studied in detail in experimental settings [ 27 ]. It was observed that after the initial lower viral loads, the loads of both nGPV and DuCV in dually infected birds were higher compared to those infected with only one pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…DuCV is an important co-factor in duck enteritis virus, goose parvovirus, and Riemerella anatipestifer infections (Neale et al, 2022), but the mechanism by which the virus causes the disease is not fully understood. DuCV infection combined with goose parvovirus increases the prevalence of short beak and dwarfism syndrome in meat-type ducks (Liu et al, 2020). The disease induced by DuCV may result from virus-induced immunopathological disorders.…”
Section: Introductionmentioning
confidence: 99%